Identification of an archaeal presenilin-like intramembrane protease. - Celia Torres-Arancivia; Carolyn M Ross; Jose Chavez; Zahra Assur; Georgia Dolios; Filippo Mancia; Iban Ubarretxena-Belandia (PLoS ONE, 2010)
BACKGROUND: The GXGD-type diaspartyl intramembrane protease, presenilin, constitutes the catalytic core of the γ-secretase multi-protein complex responsible for activating critical signaling cascades during development and for the production of β-amyloid peptides (Aβ) implicated in Alzheimer's disease. The only other known GXGD-type diaspartyl intramembrane proteases are the eukaryotic signal peptide peptidases (SPPs). The presence of presenilin-like enzymes outside eukaryots has not been demonstrated. Here we report the existence of presenilin-like GXGD-type diaspartyl intramembrane proteases in archaea. METHODOLOGY AND PRINCIPAL FINDINGS: We have employed in vitro activity assays to show that MCMJR1, a polytopic membrane protein from the archaeon Methanoculleus marisnigri JR1, is an intramembrane protease bearing the signature YD and GXGD catalytic motifs of presenilin-like enzymes. Mass spectrometry analysis showed MCMJR1 could cleave model intramembrane protease substrates at several sites within their transmembrane region. Remarkably, MCMJR1 could also cleave substrates derived from the β-amyloid precursor protein (APP) without the need of protein co-factors, as required by presenilin. Two distinct cleavage sites within the transmembrane domain of APP could be identified, one of which coincided with Aβ40, the predominant site processed by γ-secretase. Finally, an established presenilin and SPP transition-state analog inhibitor could inhibit MCMJR1. CONCLUSIONS AND SIGNIFICANCE: Our findings suggest that a primitive GXGD-type diaspartyl intramembrane protease from archaea can recapitulate key biochemical properties of eukaryotic presenilins and SPPs. MCMJR1 promises to be a more tractable, simpler system for in depth structural and mechanistic studies of GXGD-type diaspartyl intramembrane proteases.